The Role of Christian Teachers in Providing for the Needs of High-Achieving Students - Anditya, Novia Hoki; Panggabean, Meicky Shoreamanis; Dirgantoro, Kurnia P.S. (Universitas Pelita Harapan, 2017)
In every classroom, there are some students who perform better than their peers and are even very successful in most of their subjects. They are known as high-achieving students. They are grade conscious and sensitive to their teacher’s qualities. However, data from PISA 2012 shows that teachers in Indonesia cannot meet the needs of high-achieving students. High-achieving students tend to put high expectations on their teachers. From a Christian perspective, they study wholeheartedly and Christian teachers need to guide these high-achieving students so they can reach their maximum potential in a way that is pleasing to God. The purpose of this literature review is to examine what high-achieving students need from their teachers. There are five needs that high-achieving students need to have provided by their teachers: challenging assignments, self-acknowledgement, encouragement, opportunity to join in academic competitions, and learning community involvement. The responsibilities of teachers of high-achieving students should not stop with showing professionalism in meeting their expectations, but should include helping these students learn the right way of studying that is pleasing to God and not self-centered in achieving their own goals.ABSTRAK BAHASA INDONESIA: Di setiap ruang kelas, terdapat siswa-siswa yang menunjukkan performa akademik yang lebih baik dari teman-temannya atau bahkan sangat berhasil dalam semua mata pelajaran. Mereka dikenal sebagai anak yang berprestasi tinggi. Mereka sangat peduli terhadap nilai dan sensitif terhadap kualitas guru. Namun, data dari PISA 2012 menunjukkan bahwa guru-guru di Indonesia tidak dapat memenuhi kebutuhan anak-anak yang berprestasi tinggi. Anak-anak yang berprestasi tinggi cenderung menaruh ekspektasi yang tinggi dari gurunya. Dari sudut pandang Kristiani, apa yang mereka lakukan adalah salah satu bentuk pertanggungjawaban iman untuk belajar dengan sepenuh hati dan guru Kristen perlu untuk membimbing anak berprestasi tinggi dalam mencapai potensi maksimal dari diri mereka di jalan yang berkenan di hadapan Tuhan. Tujuan dari kajian literatur ini adalah untuk menguji apa yang diperlukan oleh anak berprestasi tinggi dari guru mereka. Terdapat lima kebutuhan anak berprestasi tinggi yang perlu disediakan dari guru mereka; tugas yang menantang, pengakuan diri, dukungan, kesempatan untuk bergabung dan dukungan dalam kompetensi akademik, keterlibatan dari komunitas belajar. Tanggung jawab guru Kristen tidak hanya berhenti dalam menunjukkan profesionalitas untuk memenuhi ekspektasi mereka, tapi juga membawa mereka ke jalan yang benar dan berkenan bagi Tuhan dalam belajar yaitu dengan tidak menjadi berpusat hanya kepada diri sendiri dalam mencapai tujuan mereka.